Core Elements of National Reports - Ellis, Jane (OECD/IEA Climate Change Expert Group Papers, 2010)
The UN Framework Convention on Climate Change (UNFCCC) and its Kyoto Protocol established reporting requirements for Parties. This has resulted in comprehensive and timely information on national greenhouse gas (GHG) emissions from Annex I Parties, periodic reporting of other information from Annex I Parties and irregular provision of GHG emissions and other information from non-Annex I Parties. Thus, the current reporting framework does not enable a complete or up-to-date assessment of current global GHG emissions, goals, projected future emission trends or mitigation actions and their effects. This paper explores options for the functions, form, timing and content of future national reports under the UNFCCC, focusing on national communications. It suggests that reporting guidelines for future national communications could be "tiered". This could allow countries to produce national communication "updates" on a frequent (e.g.